Hubungan dan Cara Kerja Bahasa dengan Otak Manusia - Fikria, Shayla Naina; Rumapea, Vanni Sulastri Dewi; Noviyanti, Silvina (LPPM Institut Pendidikan Nusantara Global, 2025)
The brain plays an important role in the language process in humans, both in processing oral and written information. In oral information, sound is processed in the temporal lobe and forwarded to Wernicke's area to be interpreted. If a verbal response is needed, this interpretation is sent to Broca's area via the arcuate fasciculus. This is different from written information which is directly processed in the visual cortex (occipital lobe) before being forwarded to Wernicke's area via the angular gyrus. In addition, the left hemisphere of the brain is more dominant in language function. Disorders in the left hemisphere can cause decreased language ability. Conversely, disorders in the right hemisphere have a greater effect on narrative and inference abilities. This article also discusses speech disorders that occur due to brain damage, such as aphasia caused by stroke.